Missing the mark: Dimona and Egypt's slide into the 1967 Arab-Israeli War. Issue 5 (2nd September 2018) - Elbahtimy, Hassan
ABSTRACT: Did nuclear considerations play an important role in the outbreak of the 1967 Arab-Israeli War? This research article seeks to answer this question by examining Egyptian decisions and conduct during the crisis preceding the war. The article argues that, despite long-standing Egyptian concerns over Israeli nuclear ambitions, the issue played only a marginal role in Egypt's path to war. Egypt's slide into war was a result of miscalculation rather than a deliberate plan to destroy Dimona. During the pre-war crisis, the nuclear dimension played only a minor role in Egyptian military planning. While a contingency plan to target Dimona was studied, it was never implemented. The article predominantly draws on Arabic-language sources, including first-hand accounts of Egyptian decision making during the pre-war crisis.